The Potency of Vitamin C in Tomato Plant for the Result of Genetically Modified Lanceolate Gene Through Agrobacterium Tumefaciens Using CRISPR-CAS 9 - Vannesa El Shaday Ruth Advenita; Christeven Mevotema; Iren Asima Situmorang; Lusiana Haris; Wahyu Irawati (Jurnal Biologi Tropis, 2023)
Vitamin C is the important part in the formation of protein in the body, one of which is obtained from tomatoes (Solanum lycopersicum L.). Due to the needed of vitamin C, a way is needed to get vitamin C from tomatoes which are of higher value. Tomato genetically modified using the lanceolate gene through Agrobacterium tumefaciens using CRISPR-CAS9 is a promising solution for the food world. The literature study method is carried out by reviewing the theory and the results of previous research qualitatively. The results is that genetically engineered tomatoes have the advantage of high vitamin content by using plant improvement and modification. The bacterium Agrobacterium tumefaciens functions as a vector and insertion site for recombinant genes and CRISPR-CAS9 technology is used to modify the target genome because it has a CAS9 protein containing two homologous domains resulting in a new trait. Tomatoes with lanceolate leaves will have fruit with high vitamin content because the results of photosynthesis are focused on fruit development. Suggestions for conducting in-depth research to ensure safety in the food quality and health. The goals of the research were to 1) determine the potency of tomato rich in vitamin C using genetic engineering of Agrobacterium tumefaciens, 2) structure and function of the Lanceolate gene in plants, 3) application of CRISPR-CAS 9 in genetic engineering, and 4) advantages and disadvantages of genetically modified tomato. God gave humans the ability to manage His creation. So that humans can glorifying God through research.